Opportunities and challenges in the treatment of IgA nephropathy - Yang, Yang; Xu, Gaosi (Frontiers in Pharmacology, 2025)
The treatment paradigm of immunoglobulin A nephropathy (IgAN) is shifting, and traditional therapeutic strategies are insufficient to meet clinical needs. Based on the increasing understanding of the pathogenesis of IgAN, current treatment goals concentrate on anti-inflammatory and targeted therapy, as well as optimizing therapy. New therapeutic approaches are being developed, including complement inhibitors, B-cell activating factor and a proliferation-inducing ligand inhibitor, and endothelin receptor antagonists. Further supportive care showed promising prospects and combination therapy such as sodium-glucose cotransporter 2 inhibitor with endothelin receptor antagonists are also being investigated, which may provide greater benefit. IgAN is a disease that requires lifelong management, the treatment choices faced may be inconsistent at different ages and periods. With the emerging opportunities in IgAN treatment, achieving individualized precision therapy is a key challenge currently facing research institues. This review summarizes recent advances in the treatment of IgAN and discusses possible therapeutic strategies for IgAN patients.